Alimentação de Potamotrygon signata e Potamotrygon orbignyi (Chondrichthyes: potamotrygonidae) na bacia do rio Parnaíba. - Moro, Guilherme (2010)
The evaluation of this diet, based on stomach content analisys, has already became rutine practice in fish ecology studies. The family Potamotrygonidae, represented by all Neotropical fresh water sting rays, is considered the only eslamobranch family whose members are totally restricted and adapted to this enviroment. The samples were obtained in the months of February, September, November of 2009 and April of 2010, in the Parnaiba river basin. Therefore, the stomach content of 59 specimens of P. signata (36 females and 23 males) and the 23 examples of P. orbignyi (12 females and 11 males) were analysed from sites in the State of Piaui. Of all the examples colected of both species, only P. signata presented the 3 empty stomachs. The repletion level 2 (halfway full) was the most representative for P. signata, while in the mean time, P. orbignyi was level 1 (¼ full). Most food items for both species presented digestion level 3 (external parts and muscle mass partially digested). The identification of the food items for P. signata indicated the presence of 13 orders, including insects, crustaceons, molluscs and fish. However, the IRI% of the specie showed a food preference for diptera (Chironomidae) and Ephemeroptera (Ephemeridae) larvae. P. orbignyi presented a much less diverse diet, including only 3 insects orders (diptera, ephemeroptera and odonata). Differences between males, females, youngs and adults diets were verified for both species. In a general, P. signata and P. orbignyi are preferably insectivorous.